Islamic Education Foundation: An Axiological Philosophy of Education Perspective - Arti Sri Rahayu (International Journal of Nusantara Islam, 2016)
This article is a literature study (library research), which aims to assess the qualitative description of the basis of Islamic education Axiological if viewed in the perspective of philosophy of education. To obtain the results of the study, the researcher uses several methods, among others: deductive, inductive, historical, and contextual. The type of research using library research (library research) with descriptive-analytic approach to data (primary and secondary) are qualitative. The results obtained is that Islam is the sistem of values that guide the Islamic way of life, in accordance with the guidance of Allah SWT. Axiology cornerstone of Islamic Education with regard to values, goals, and targets to be achieved in Islamic education. Those values must be included in the curriculum of Islamic education, among others: contains instructions morals; efforts for improving the welfare of human life on earth and happiness in the hereafter; contains endeavor to achieve a good life; contains values that can combine the interests of this world and the hereafter. So axiology Islamic education is understood as the value, benefits or educational function of Islam associated with various things in it. Islamic values that can be obtained from two main sources namely the Qur'an and the Sunnah of the Prophet became a reference of the concepts laden education and moral values of humanity itself. So, will created the order of life "future society" is so envisioned as something new to mankind.